Negative regulation of ATP-induced inflammasome activation and cytokine secretion by acute-phase proteins: A mini review - Richter, Katrin; Amati, Anca-Laura; Padberg, Winfried; Grau, Veronika (Frontiers in Pharmacology, 2022)
The expression of the acute-phase reactants C-reactive protein (CRP), α1-antitrypsin (AAT), and secretory leukocyte protease inhibitor (SLPI), is induced in response to inflammation by pro-inflammatory mediators, including interleukin-1β. It is conceivable that acute-phase proteins exert protective functions, when the integrity of an organism is challenged by pathogens or trauma, which result in uncontrolled release of endogenous damage-associated molecular patterns like Toll-like receptor agonists and ATP. Acute-phase proteins can enhance or down-modulate immunity against infections or protect the host against damage caused by over-shooting effector functions of the immune system. CRP is mainly regarded as a pro-inflammatory opsonizing agent that binds to bacteria and damaged host cells thereby contributing to their inactivation and elimination. AAT and SLPI are well known for their anti-protease activity, which protects the lung extracellular matrix against degradation by proteases that are released by activated neutrophil granulocytes. In addition, there is growing evidence, that CRP, AAT, and SLPI can control the biosynthesis, maturation, and secretion of pro-inflammatory cytokines. The purpose of this narrative mini review is to summarize these anti-inflammatory functions with a focus on the negative control of the ATP-induced, inflammasome-dependent secretion of interleukin-1β by monocytes. CRP-, AAT- and SLPI-mediated control of interleukin-1β release involves the activation of unconventional nicotinic acetylcholine receptors that inhibits the ionotropic function of the ATP receptor P2X7. Apart from other functions, CRP, AAT, and SLPI seem to be central elements of systemic negative feedback loops that protect the host against systemic hyperinflammation, barrier dysfunction, and death by multiple organ damage.